Clinical focus and public accountability in English NHS Trust Board meetings. (January 2013) - Endacott, Ruth; Sheaff, Rod; Jones, Ray; Woodward, Valerie
Background: Previous studies have suggested that greater focus on clinical matters in NHS commissioner and provider Trust Board meetings might improve the range, quality or cost of clinical care. This study reports the extent of clinical focus in Board meetings in three types of NHS Trust and considers the implications for public accountability. Methods: (1) Content analysis of published minutes of Board meetings from 105 randomly selected NHS Trusts in 2008/09. (2) Structured observation of 24 Board meetings in a qualitative sub-sample of eight of the above Trusts in 2008/09. Results: The percentage of clinical items among the items discussed by NHS Trust Boards ranged from 0% to 51%, but did not differ by Trust type. Primary Care Trusts (PCTs) recorded more items than NHS Trusts and NHS Foundation Trusts because of PCTs' dual role as service providers and commissioners. There were significant differences between Trusts' board meetings in the numbers of clinical items concerning service design, clinical outcomes and activity levels. The availability and accessibility of supposedly publicly-available minutes from NHS Foundation Trust Board meetings was sometimes problematic. Observation of meetings revealed a number of dynamics not evident in the minutes. Board meetings were generally chair-led (conducted according to the chair's discretion); collegial; had similar levels and extent of discussion from the non-executive directors, with a focus on current policy initiatives. Boards differed in the extent of public questioning, how they exercised internal governance over the provision and quality of patient care, and the extent of pre-planning before the Board meeting. Published minutes were not always an accurate record of meetings. Conclusions: Findings illuminate important transparency issues which should be given careful consideration in the English NHS.